Hippocampus and amygdalar volumes in patients with refractory obsessive-compulsive disorder - Atmaca, Murad; Yildirim, Hanefi; Ozdemir, Huseyin; Ozler, Sinan; Kara, Bilge; Ozler, Zuhal; Tezcan, Ertan (Pergamon-Elsevier Science Ltd, 2008)
Functional and structural neuroimaging studies have implicated the hippocampus-amygdala complex in the pathophysiology of obsessive-compulsive disorder (OCD), although no consensus has been established. These brain regions have not been investigated in refractory OCD patients. Volumes of the hippocampus, and amygdala were measured by magnetic resonance imaging (MRI) in a sample of 14 refractory OCD patients and 14 healthy comparison subjects. The mean left and right hippocampal and amygdala volumes of the patients were smaller than those of the healthy controls. OCD severity was not correlated with amygdala volumes but was related to the left hippocampus. Duration of illness was correlated with both hippocampus and left amygdala. Our findings suggest that hippocampus and amygdalar abnormalities can be considered in refractoriness to OCD. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: MRI; hippocampus; amygdala; volumetric